Analysis of Women's Quota in DPRD Province of DKI Jakarta : Period 2014-2024 - Risda Trully Tobing; Mardi Siswoyo; Laras Ati; Freddy J Rumambi; Marisi Pakpahan; Pingkan Luciawati Sompi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to analyze the implementation and effectiveness of the women's quota in the Regional House of Representatives (DPRD) of DKI Jakarta Province during the 2014-2024 period. The women's quota is an affirmative policy designed to increase women's representation in the legislature, regulated by Indonesia's electoral law. Although this policy has been implemented, there are still various challenges that hinder women's participation in politics, including cultural, social, and structural barriers. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with Deputy Chairman of DPRD , Legislative Candidate, Academics , Sociologist and Law/ Political observers, as well as analysis of official documents and related reports. The results show that despite an increase in the number of women in the Regional House of Representatives (DPRD ) of DKI Jakarta Province , the women's quota has not fully achieved its goals. Some of the factors that affect the effectiveness of this quota include the lack of support from political parties, strong gender stereotypes, and obstacles in the recruitment and selection process of female candidates. This research also found that the existence of women's quotas alone is not enough to increase women's participation in politics. Further efforts are needed, including political education for women, capacity building for female legislator candidates, and reforms in the political party system to support greater involvement of women. In conclusion, the women's quota in the Regional House of Representatives (DPRD) of DKI Jakarta Province still faces various challenges in its implementation, and additional strategies are needed to overcome these obstacles in order to achieve more equitable and inclusive representation.